Docência e geografia escolar: espaço, tempo e possibilidades - Barbosa, Maria Edivani Silva (2014)
Understanding the art of teaching, the teaching of Geography and the school inserted in the social contemporaneous context and also in real situations of work was the greatest challenge of this research, that had as the main concern the fact of getting to know how the teachers mobilize themselves in schools considering that these schools are organized in order to follow the principles that are the foundation of the traditional curriculum, above all, the organization of space, and the school´s periods of time. As a general objective, the challenges and the obstacles for the practice of teaching including the teaching of geography imposed to the schools, to the teachers and to students were analysed considering the context of a society that is completeley led by technological resources and the mainstream media. The theoretical approach is inscribed in the field of theoretical critic and follows the strand developed by Giroux (1983,1986,1988,1997). Starting from this theoretical carcase the concepts of school were considered as a public democratic sphere, intelectual, critical and transformer professors, resistence and possibilities. The nature of the approach is qualitative using the kind of method of descriptive study in a public school of Fortaleza city – CE. The collect of data occured in 2013 with documental analysis, bibliographical research, interviews according to the referred issue, application forms with questionnaires, observing the classrooms, schools spaces, and photografic registers. The study revealed that the organization of time and spaces in schools are inspired in a sequenced and disciplinar model in a routine that subdivides the time in equal periods of time for all. Coletiv time that reproduces a basic pattern of periods of work in class, coffee breaks, and acitivities of preparation for the teachers. The spaces like halls, sports court, classrooms, informatics classroom, are small and cramped and even without mentioning the shortage of pedagogical resources.In order to attend the demands prescribed in the academic books of geography, guidelines, and school parameters. It was also verified that the teachers use creative strategies to overcome the obstacles and challenges of the school. The teachers are mobilized by a critical language when United to a language of possibility makes them motivated to go on and don´t give up, and to face the daily challenges, trying to make the floor of the school a space of transformation. It was highlighted the possibility of the quality improvement about the teaching of geography in basic education, by the maximization of school environment and for the practical knowledge of the teachers.